Predictability and Accuracy in Adaptive User Interfaces - Gajos, Krzysztof; Everitt, Katherine; Tan, Desney; Czerwinski, Mary; Weld, Daniel (Extended Abstracts of CHI 2008 Conference on Human Factors in Computing Systems, 2008)
While proponents of adaptive user interfaces tout potential performance gains, critics argue that adaptation's unpredictability may disorient users, causing more harm than good. We present a study that examines the relative effects of predictability and accuracy on the usability of adaptive UIs. Our results show that increasing predictability and accuracy led to strongly improved satisfaction. Increasing accuracy also resulted in improved performance and higher utilization of the adaptive interface. Contrary to our expectations, improvement in accuracy had a stronger effect on performance, utilization and some satisfaction ratings than the improvement in predictability.